Alternative settlement of dispute between Israel and Palestine - Narita Tarasari; Addelia Aizah R; Ajeng Althafira A; Zahra Nasywa; Fikri Fajar M (Goodwood Publishing, 2021)
Purpose: This research purpose is to find an alternative dispute between Israel and Palestine so that human rights are not being deprived anymore. Research methodology: The approach in this study was carried out by deepening research by reading literature related to the problem that became the topic, namely the dispute between Palestine and Israel. Results: The results obtained from this study are that the dispute between Israel and Palestine is still experiencing obstacles in the implementation of resolution no. 181 so that there is a need for follow-up from the UN security council and the UN general assembly so that the dispute can be resolved immediately Limitations: This research has not explained how the implementation of the solution that has been given. Contribution: Analyze how the right way to resolve the conflict between Israel and Palestine.